Nanocurcumin Enhances Antioxidant Defense through GPx Upregulation in Ovarian Granulosa Cells of Endometriosis Mouse Model - Haspita Rizki Syurya Handini; Hendy Hendarto; Bambang Purwanto; Widjiati Widjiati (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Endometriosis impairs female reproductive function through oxidative stress and apoptosis, reducing oocyte quality and causing infertility. Current therapies are limited by suboptimal efficacy and side effects, including ovulation suppression. Curcumin offers antioxidant and anti-inflammatory benefits but has low bioavailability and poor solubility, which can be improved through nanoparticle formulation. Although nanocurcumin is suggested to act through multiple pathways, its mechanisms remain unclear. This study was conducted to evaluate the antioxidant and anti-apoptotic effects of nanocurcumin in a mouse model of endometriosis.METHODS: Thirty-five mice were allocated into five groups and induced to develop endometriosis using cyclosporine A, ethinyl estradiol, and human endometrial tissue. Nanocurcumin was formulated at three particle sizes (3.71; 3.98; and 25.60 nm) and administered orally at doses of 50, 100, or 200 mg/kg/day for 14 days. After treatment, the mice were euthanized, and ovarian tissues were collected for immunohistochemical analysis of glutathione peroxidase (GPx) and B-cell lymphoma-2 (Bcl-2) expression.RESULTS: The highest GPx expression was observed in the group receiving 50 mg/kg/day nanocurcumin (mean±SD= 6.31±1.97; p=0.042). The lowest expression of Bcl-2 was observed in control group with no treatment (mean±SD=4.15±2.48; p=0.582). Nanocurcumin administration significantly increased GPx expression in a dose-dependent manner compared with the untreated group, while no significant differences were found in Bcl-2 expression.CONCLUSION: Nanocurcumin increases GPx expression, particularly at 50 mg/kg/day, indicating its potential as an antioxidant in reducing oxidative damage associated with endometriosis. However, nanocurcumin did not significantly influence Bcl-2 expression. These findings support nanocurcumin’s role as an effective antioxidant agent in protecting ovarian granulosa cells in endometriosis.KEYWORDS: nanocurcumin, GPx, Bcl-2, endometriosis, granulosa cells